Evolocumab safety and efficacy in hypercholesteremia patients with or without diabetes: a retrospective real-world analysis - Sultan Ibrahim Alraddadi; Hind Almodaimegh; Abdullah Kharbosh; Hadeel Alharbi; Ahmed Ibrahim Fathelrahman; Mona Yaser Alsheikh; Lama Alfehaid (Diabetology & Metabolic Syndrome)
Abstract Background Proprotein convertase subtilisin/kexin type 9 inhibitors effectively reduce LDL cholesterol and adverse cardiovascular events with a safety profile comparable to a placebo. Limited real-world data exists on their effectiveness in different patient groups. This study evaluated evolocumab’s efficacy and safety in hypercholesteremia patients with and without diabetes. Method In a large tertiary hospital in Saudi Arabia, patients aged 18 and above who initiated evolocumab therapy were screened for eligibility between January 2017 and July 2023. All patients who had been on maximally tolerated statin and ezetimibe therapy for at least 4 months before starting evolocumab were included. The included participants were then divided into diabetic and non-diabetic groups and assessed for evolocumab’s efficacy and safety. Efficacy was measured by LDL-C reduction and target achievement, while safety was assessed by examining glycemic control changes, new-onset diabetes (NOD) and hepatic enzyme levels. Data analysis included descriptive and comparative methods, with significance set at p < 0.05. Results A total of 151 patients were included, with an average age of 51.77 years. The majority of patients were male (67.6%) and obese (81.5%). Around 55% had diabetes, and 63% had established atherosclerotic cardiovascular disease at baseline. During a mean follow-up period of 13.17 months, the average reduction in LDL-C from baseline was − 34.21, − 28.66, and − 39.61% for the overall cohort, non-diabetic patients, and diabetic patients, respectively. In the overall cohort, 34.4 and 24.5% reached the target LDL-C levels of less than 1.4 mmol/L (55 mg/dL) and less than 1.8 mmol/L (70 mg/dL), respectively. Worsening of glycemic control (HbA1C increase > 0.5) was observed in 25.83% of the overall cohort, 16.18% of non-diabetics, and 33.74% of diabetics. An HbA1C increase > 1 was observed in 13.25% of the overall cohort, 2.94% in non-diabetics and 21.69% in diabetics. Five patients (3.3%) developed NOD. Conclusion The study demonstrated that the addition of evolocumab to maximally tolerated statin and ezetimibe therapy reduced LDL-C levels but with a smaller average reduction and a lower proportion of patients achieving recommended LDL-C targets than in landmark clinical trials. Additionally, there was a potential negative effect on glycemic control, warranting further investigation.